Role of Biofilms in Chronic Surgical Wound Infections - Russell, Abu Taher Mohammad; Azam, Md Ali; Islam, Ryhan; Mia, Mohammad Salauddin; Islam, Muhammad Moinul (Community Based Medical Journal, 2026)
Chronic surgical wound infections (CSWIs) remain a major clinical challenge due to biofilm formation, which contributes to antibiotic resistance and delayed healing. Despite growing recognition of biofilms in persistent infections, limited data exist on their prevalence and impact in low-resource settings. This prospective, cross-sectional study was conducted at 250-bedded district hospital and Sreepur Upazilla Health Complex in Magura district of Bangladesh, between July 2024 and June 2025, to evaluate the role of biofilms in CSWIs, assessing their association with wound chronicity, microbial resistance, and clinical outcomes. A total of 287 patients with CSWIs were enrolled via purposive sampling. Wound swabs were analyzed using culture, Gram staining, and microscopy to detect biofilms. Clinical and microbiological data were recorded and analyzed. Among 287 CSWI patients (mean age 52.4±12.8 years), biofilm prevalence was 78.4%, significantly higher in diabetics (84.6% vs 68.2%, p=0.003). Staphylococcus aureus (32.4%) and Pseudomonas aeruginosa (24.7%) dominated biofilm-positive isolates, showing 85.2% antibiotic resistance versus 41.9% in biofilm-negative cases (p<0.001). Biofilm-associated wounds required longer healing (42.6±18.3 vs 28.5±14.7 days, p<0.05) and showed 3.1-fold increased recurrence risk (p<0.05). Diabetes mellitus (OR=2.6) and poor wound care (OR=3.1) predicted biofilm formation. Biofilms were highly prevalent in CSWIs, strongly associated with antibiotic resistance and delayed healing. Diabetes mellitus and inadequate wound care emerged as key risk factors. These findings underscore the need for biofilm-targeted management strategies in surgical wound care, particularly for high-risk populations in resource-limited settings. CBMJ 2026 January: vol. 15 no. 01 P:41-45